Biochemical study of some microalgae and using it production of biofuel - Muhanad H. S. Al-Jubori; Jihad D. M. Al-Janabi; Youssef J. I. AI-Shahrii (Tikrit Journal of Pure Science, 2023)
The present study includes growing five species of microalgae which are Chlorella sacchrophila, Chlorella  vulgaris ,  Scendesmus  obliquus ,  Botryococcus  braunii  and Chlamydomonas reinhardtii algae and using it of figure out processing biofuels. The study is considered as a seldom study in Iraq. The study is chose and focused for its high scientific and economical value.